Iron cycling during the autocatalytic decomposition of benzoic acid derivatives by Fenton-like and photo-Fenton techniques - Nichela, Daniela A. (2015)
In the context of our work on the oxidative degradation of a series of hydroxyl derivatives of benzoic acid(HBAs) by Fenton-like and photo-Fenton processes, we present a comprehensive study of the factors thataffect the reduction of Fe(III) species, the rate limiting step in the Fenton reaction. We have investigated:(i) the formation of Fe(III)–HBA complexes, (ii) the ability of these complexes to participate in reductivepathways, and (iii) the formation of intermediate products capable of reducing ferric species.The results show that salicylate-like HBAs form stable bidentate ferric complexes in aqueous solutionsat pH 3.0 and that Fe(III) complexation significantly decreases the overall degradation rates in Fenton sys-tems by slowing down Fe(II) production through both dark and photo-initiated pathways. Interestingly,in contrast to ferric complexes of aliphatic carboxylates that undergo a photo-induced decarboxyla-tion upon excitation in the 300–400 nm wavelength range, ferric–salicylate complexes yield Fe(II) andhydroxyl radicals by oxidation of water molecules in the coordination sphere of the metal center. How-ever, their efficiencies are significantly lower than that of the Fe(III) aqua complex. Moreover, Fe(III)–HBAcomplexes are inert upon excitation of the LMCT bands involving the organic ligand (i.e., 400–600 nm).As observed for other aromatic compounds, Fe(III)-reducing intermediates formed during the Fentonoxidation of HBAs play a key role in iron cycling. The analysis of the primary oxidation/hydroxylationproducts as well as Fe(III)-reduction studies showed that, among dihydroxy aromatic derivatives,hydroquinone-like structures were much more efficient than catechol-like structures for reducing Fe(III).Although all trihydroxy derivatives produced Fe(II), ring opening reactions prevailed under the conditionsof the Fenton reaction.The results of our investigation on the Fenton oxidation of HBA derivatives show that, in each particularcase, the complex interplay of the aforementioned factors should be carefully evaluated for developingoptimal applications of Fenton processes at a technological level.